The Epistemology of Javanese Qurâanic Exegesis: A Study of á¹¢Äliá¸¥ Daratâs Fayá¸ al-Raá¸¥mÄn - Mustaqim, Abdul (Al-Jamiah: Journal of Islamic Studies, 2017)
This article seeks to analyse the structure of the epistemology of Fayá¸ al-Raá¸¥mÄn, a Javanese Qurâanic-exegetical work by á¹¢Äliá¸¥ Darat, a prominent Javanese ulama in the nineteenth century. It is the only Javanese Qurâanic-exegetical work (kitÄb al-tafsÄ«r) with the Sufi-esoteric interpretation (al-tafsÄ«r al-á¹£Å«fi al-ishÄrÄ«). Yet, there has not been research discussing its epistemology of interpretation whereas it is significant to grasp its fundamental structure of thought. Employing historical-philosophical approach, this article argues that Fayá¸ al-Raá¸¥mÄnâs exegesis reflect the illuminative epistemology (âirfÄni) by which á¹¢Äliá¸¥ Darat does not only explain the textual meaning (al-maânÄ al-áºÄhir) but also the esoteric meaning (al-maânÄ al-ishÄrÄ«) of the Qurâan. In á¹¢Äliá¸¥ Daratâs view, the relation of the two resembles the relation between spirit and body that cannot be separated. The esoteric interpretation thus constitutes revealing inner meanings of the Qurâan. According to á¹¢Äliá¸¥ Darat, the ideal interpretation is to grasp both the textual and esoteric meaning of the Qurâan. With the Sufi-esoteric interpretation, á¹¢Äliá¸¥ Darat truly intends to bridge the epistemological polemics between Muslim jurists (fuqahÄâ) who are inclined to the textual meaning and Sufi-philosophers who are inclined to the esoteric meaning. Besides, written in Arabic-pegon script, á¹¢Äliá¸¥ Daratâs Fayá¸ al-Raá¸¥mÄn fortifies the Javanese cultural identity in the sense that Javanese Qurâanic exegesis have equal authority as Arabic Qurâanic exegesis. This also reflects the cultural strategy to oppose the policy of the Dutch colonialism that enforced the use of Latin alphabet on behalf of bureaucracy and correspondence at the time.[Artikel ini mendiskusikan tentang struktur epistemologi tafsir Fayá¸ al-Raá¸¥mÄn karya á¹¢Äliá¸¥ Darat. Kitab tersebut merupakan satu-satu kitab tafsir berbahasa Jawa dengan corak tafsir sufi isyari. Namun demikian, selama ini belum ada riset-riset terdahulu yang mengkaji tentang isu epistemologi tafsirnya. Padahal, dengan mengkaji epistemologinya, kita akan memahami struktur fundamental pemikirannya. Dengan pendekatan historis-filosofis, artikel ini berargumen bahwa epistemologi tafsir Fayá¸ al-Raá¸¥mÄn mencerminkan epistemologi âirfÄni (illuminasi) dengan corak tafsir sufi isyari. Ketika menafsirkan al-Qurâan, á¹¢Äliá¸¥ Darat tidak hanya menjelaskan dimensi makna zahir ayat, tetapi juga makna batinnya. Baginya, relasi keduanya tidak dapat dipisahkan, ibarat tubuh dan ruh. Sehingga, penafsiran al-Qurâan menjadi lebih hidup dan mendalam. Penafsiran yang ideal ialah manakala mampu menangkap kedua makna tersebut secara sinergis. Dengan corak tafsir sufi isyari, á¹¢Äliá¸¥ Darat sebenarnya ingin mendamaikan konflik epistemik antara kaum fuqahaâ yang hanya berorietasi pada makna zahir dan kaum sufi yang hanya berorientasi pada makna batin. Di sisi lain, penggunaan tulisan Arab-Pegon dalam kitab tafsirnya merefleksikan peneguhan identitas kultural Jawa bahwa tafsir berbahasa Jawa memiliki otoritas yang sama dengan tafsir-tafsir yang berbahasa Arab. Hal ini juga merupakan strategi kebudayaan untuk melawan kolonialisme Belanda yang ketika itu menginstruksikan agar menggunakan tulisan laitin dalam birokrasi dan surat-menyurat.]